1998
DOI: 10.1590/s0036-46651998000500008
|View full text |Cite
|
Sign up to set email alerts
|

STANDARDIZATION OF PROCEDURES OF Plasmodium falciparum ANTIGEN PREPARATION FOR SEROLOGIC TESTS

Abstract: The objective of the present study is to standardize the technical variables for preparation and storage of Plasmodium falciparum and of antigen components extracted with the amphoteric detergent Zwittergent. P. falciparum obtained from in vitro culture was stored at different temperatures and for different periods of time. For each variable, antigen components of the parasite were extracted in the presence or absence of protease inhibitors and submitted or not to later dialysis. Products were stored for 15, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…But these results also suggest possible differences in immunogenicity of the peptide epitopes as has been previously observed by others [ 39 ]. It is likely that immunoassays using extracts of total parasite lysate may find higher sero-prevalence’s in all residents of comparable endemic study areas since such whole-cell antigen extracts contain thousands of parasite antigens [ 40 42 ]. Nevertheless, the finding that all study subjects showed IgG sero-reactivity to at least one of the tested three peptides by day 42 ( Fig 1 ) suggests that antibody priming by blood-stage targeted vaccines such as GMZ2 could be boosted by the few infections experienced annually in moderate-transmission endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…But these results also suggest possible differences in immunogenicity of the peptide epitopes as has been previously observed by others [ 39 ]. It is likely that immunoassays using extracts of total parasite lysate may find higher sero-prevalence’s in all residents of comparable endemic study areas since such whole-cell antigen extracts contain thousands of parasite antigens [ 40 42 ]. Nevertheless, the finding that all study subjects showed IgG sero-reactivity to at least one of the tested three peptides by day 42 ( Fig 1 ) suggests that antibody priming by blood-stage targeted vaccines such as GMZ2 could be boosted by the few infections experienced annually in moderate-transmission endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Sera were also assayed for detection of anti‐ P. falciparum blood stage IgG antibodies as described previously by Avila et al . (12).…”
Section: Introductionmentioning
confidence: 99%
“…Results were considered positive for values greater than the mean RI of 100 sera samples from unexposed blood donors, assayed against each antigen. Sera were also assayed for detection of anti-P. falciparum blood stage IgG antibodies as described previously by Avila et al (12).…”
Section: Introductionmentioning
confidence: 99%
“…Em áreas não endêmicas, suas principais indicações estão na triagem de doadores em bancos de sangue, na elucidação de casos clínicos indefinidos, na malária críptica e na detecção de assintomáticos (Warhurst e Williams, 1996). (Sanchez et al, 1993;Ávila et al, 1998;Coelho et al, 2007), antígenos recombinantes (Medeiros et al, 2013;Riccio et al, 2013;Coelho et al, 2007) e peptídeos sintéticos de proteínas específicas do estágio eritrocítico (Graves et al, 1992;Nebie et al, 2009).…”
Section: Imunidade Na Maláriaunclassified